SQUEEZED PARTICLE-ANTIPARTICLE CORRELATIONS - Padula, Sandra S. [UNESP]; Dudek, Danuce M. [UNESP]; Socolowski, Otavio (Polish Acad Sciences Inst Physics, 2009)
A novel type of correlation involving particle-antiparticle pairs was found out in the 1990's. Currently known as squeezed or Back-to-Back Correlations (BBC), they should be present if the hadronic masses are modified in the hot and dense medium formed in high energy heavy ion collisions. Although well-established theoretically, such hadronic correlations have not yet been observed experimentally. In this phenomenological study we suggest a promising way to search for the BBC signal, by looking into the squeezed correlation function of phi phi and K(+)K(-) pairs at RHIC energies, as function of the pair average momentum, K(12) = (k(1) + k(2))/2. The effects of in-medium mass-shift on the identical particle correlations (Hanbury-Brown and Twiss effect) are also discussed.